Regeneration of the active zone at the frog neuromuscular junction (The Rockefeller University Press, 1984)
The active zone is a unique specialization of the presynaptic membrane and is believed to be the site of transmitter release. The formation of the active zone and the relationship of this process to transmitter release were studied at reinnervated neuromuscular junctions in the frog. At different times after a nerve crush, the cutaneous pectoris muscles were examined with intracellular recording recording and freeze- fracture electron microscopy. The P face of a normal active zone typically consists of two double rows of particles lined up in a continuous segment located opposite a junctional fold. In the initial stage of reinnervation, clusters of large intramembrane particles surrounding membrane elevations appeared on the P face of nerve terminals. Like normal active zones, these clusters were aligned with junctional folds. Vesicle openings, which indicate transmitter release, were seen at these primitive active zones, even though intramembrane particles were not yet organized into the normal pattern of two double rows. The length of active zones at this stage was only approximately 15% of normal. During the secondary stage, every junction was reinnervated and most active zones had begun to organize into the normal pattern with normal orientation. Unlike normal, there were often two or more discontinuous short segments of active zone aligned with the same junctional fold. The total length of active zone per junctional fold increased to one-third of normal, mainly because of the greater number of segments. In the third stage, the number of active zone segments per junctional fold showed almost no change when compared with the secondary stage. However, individual segments elongated and increased the total length of all active zone segments per junctional fold to about two-thirds of the normal length. The dynamic process culminated in the final stage, during which elongating active zones appeared to join together and the number of active zone segments per junctional fold decreased to normal. Thus, in most regions, regeneration of the active zones was complete. These results suggest that the normal organization of two double rows is not necessary for the active zone to be functional. Furthermore, localization of regenerating active zones is related to junctional folds and/or their associated structures.